Diagnóstico del Potencial Endógeno de la parroquia rural Santiago del cantón Loja: período de estudio 2017-2018 - Bravo Jiménez, Arturo José. (2018)
The rural parish of Santiago de Loja is located 33 km from the urban area, it is made up of eighteen neighborhoods, the climate and the geographical location allow a diversity of flora and fauna; as well as an agricultural and livestock production in an organic and healthy way; It has a variety of attractive natural and cultural resources, is characterized by the predominance of the Catholic faith that results in a great diversity of customs and traditions. The results show that the existing development models respond to the needs of each locality as long as these allow to enhance the territorial capacities, whatever the objective of the analysis of the economic development, to a large extent, only reflect on purely economic aspects "ignoring in general, social, political aspects "to this we would have to add human, cultural, environmental and religious aspects; otherwise, the mechanisms and public policies of development applied will be resisted by the population, so it will be necessary to modify the model. The study of the development of the endogenous potential, allowed to elaborate a diagnosis "of the endogenous potential of the rural parish of Santiago", since it allows the local development through exploitation of the potential of endogenous resources of a determined territorial space, to detect, use and activate the same, by a possible set of local change agents, from the analysis of development models in a timeline.